2006
DOI: 10.1111/j.1399-6576.2006.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thoracic intervertebral spaces by means of surface anatomy: a magnetic resonance imaging study

Abstract: We recommend that the caudal of two to three possible interspaces should be used when placing an epidural catheter in the thoracic spine. Because of the inaccurate localization of the thoracic intervertebral spaces, documentation should state the site of puncture as being in the upper or lower thoracic spine instead of claiming to be in an exact interspace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…In identifying thoracic interspaces, Holmaas et al 17 found an agreement of 26.7% between the clinical palpatory method and magnetic resonance imaging (MRI), while Teoh et al 18 found a 10% agreement between the scapular tip and T7 spinous process when using chest radiography to confirm the clinical palpatory method. For a two-sided type I error of 5% and a type II error of 20%, 45 subjects were needed to estimate the rate of agreement between the ultrasound and palpatory techniques within the range of the above mentioned results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In identifying thoracic interspaces, Holmaas et al 17 found an agreement of 26.7% between the clinical palpatory method and magnetic resonance imaging (MRI), while Teoh et al 18 found a 10% agreement between the scapular tip and T7 spinous process when using chest radiography to confirm the clinical palpatory method. For a two-sided type I error of 5% and a type II error of 20%, 45 subjects were needed to estimate the rate of agreement between the ultrasound and palpatory techniques within the range of the above mentioned results.…”
Section: Discussionmentioning
confidence: 97%
“…17 Similarly, a study to compare palpation of surface landmarks with chest radiography in patients in the anatomic position found that both the vertebra prominens and the scapular tip were inaccurate landmarks for identifying the T7 spinous process (29% vs 10% accuracy, respectively). 18 In our study, the agreement was better in the epidural position than in the anatomic position when using the scapula as a landmark.…”
Section: Discussionmentioning
confidence: 98%
“…Vertebrae have more or less specific intervertebral spaces [16], the only problem is that on a bone scintigram only a planar projection of the spine is visible. Since the spine is longitudinally curved, the vertebral spatial relations vary due to different axial orientation of the patients.…”
Section: Thoracic Part (Vertebrae Ribs)mentioning
confidence: 99%
“…Although anatomical landmarks are useful they are often difficult to locate or palpate in patients with obesity, 1 edema in their backs, and underlying spinal deformity or after spinal surgery. Even in the absence of the above, a given intervertebral space is accurately identified in only 30% 2,3 of cases and anesthesiologists very frequently incorrectly identify a space higher than intended, 2,4,5 which has been attributed as a cause for injury of the conus medullaris 4 or spinal cord 6 after spinal anesthesia. This error is exaggerated by obesity 2 and as one tries to locate an intervertebral space in the upper spinal levels.…”
Section: Introductionmentioning
confidence: 97%
“…This error is exaggerated by obesity 2 and as one tries to locate an intervertebral space in the upper spinal levels. 2,4,5 Therefore, the Tuffier's line, a surface anatomical landmark, that is ubiquitously used during CNB is not a reliable landmark. 5 Moreover, because of the blind nature of the landmark-based techniques, it is not possible for the operator to predict the ease or difficulty of needle placement prior to skin puncture.…”
Section: Introductionmentioning
confidence: 99%